An economic policy for the fifth long wave - Reati, Angelo; Toporowski, Jan (PSL Quarterly Review, 2009)
The paper starts by reviewing some recent contributions on long waves, arguing that the present technological revolution in ICT is part of the broad phenomenon of a new long wave. It follows that the main focus of economic policy should be to support the diffusion of the new technology and to favour the institutional changes required by such an objective. Four broad guidelines are suggested: i) a Keynesian policy for demand going beyond the straitjacket of the Maastricht criteria and improving the income distribution in favour of employees; i) a policy to re-establish the primacy of productive capital through systematic concerted open market operations to regulate financial liquidity; iii) a reconstruction of the employment relationship that preserves the essential features of the "European social model" and a targeted flexibility of labour, that contrasts with the neoclassical all-out market flexibility; and iv) a regime for intellectual property rights that avoids the drawbacks--both ethical and economic--of current US practices. Paper originally published in the BNL Quarterly Review, vol. 57 n. 231, December 2004, pp. 395-437. JEL Codes: F3, G1, N1, B5